A messenger at the door: cytomegalovirus retinitis in myeloma patients with progressive disease. Issue 4 (23rd June 2013) - Teh, B.W.; Khot, A.S.; Harrison, S.J.; Prince, H.M.; Slavin, M.A.
Abstract Cytomegalovirus (CMV) retinitis is an uncommon manifestation of CMV disease and is a marker of severe and profound immunosuppression in human immunodeficiency virus‐positive patients. Here, we describe 2 cases of CMV retinitis in myeloma patients with progressive disease, following autologous stem cell transplantation and immunomodulatory therapy for myeloma. To our knowledge, this is the first report of CMV retinitis in this patient population. This report illustrates the need for close monitoring of relapsed and refractory myeloma patients for new presentations of opportunistic infections secondary to severe immunosuppression.